2011
DOI: 10.1098/rsbl.2011.0264
|View full text |Cite
|
Sign up to set email alerts
|

Birds bias offspring sex ratio in response to livestock grazing

Abstract: Livestock grazing, which has a large influence on habitat structure, is associated with the widespread decline of various bird species across the world, yet there are few experimental studies that investigate how grazing pressure influences avian reproduction. We manipulated grazing pressure using a replicated field experiment, and found that the offspring sex ratio of a common upland passerine, the meadow pipit Anthus pratensis , varied significantly between grazing treatments. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
(33 reference statements)
1
13
0
2
Order By: Relevance
“…The impact of livestock grazing on bird abundances in grasslands has long been recognized (Knopf 1994, Henderson et al 2004), but the impact of grazing intensity on the sex ratios within broods for local grassland birds have received little attention (Prior et al 2011). We found that a quadric term (GI 2 ) significantly correlated with the offspring sex ratio at fledging of an alpine-steppe passerine.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The impact of livestock grazing on bird abundances in grasslands has long been recognized (Knopf 1994, Henderson et al 2004), but the impact of grazing intensity on the sex ratios within broods for local grassland birds have received little attention (Prior et al 2011). We found that a quadric term (GI 2 ) significantly correlated with the offspring sex ratio at fledging of an alpine-steppe passerine.…”
Section: Discussionmentioning
confidence: 74%
“…The proportion of sons was lower in ungrazed and intensively grazed treatments but higher in areas with low grazing intensity. This study adds evidence of adjusted offspring sex ratio in response to habitat conditions (Suorsa et al 2003, Komdeur 2004, Prior et al 2011. To better understand the pattern we observed in sex ratios, large manipulative experiments with respect to the effect of livestock grazing will be necessary.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations